Language planning, security, police communication and multilingualism in uniform: The case of South African Police Services. (November 2017) - Makoni, Sinfree B.
Abstract: The virulence of global conflicts and conflicts between different ethnolinguistic groups makes language, now more so than previously, a central issue within the state security apparatus. Police are at the forefront of law enforcement, making language and language planning an integral component of police communication. The centrality of language is more pertinent in complex multilingual contexts like South Africa. The sociolinguistic and discourse analysis of the security in South Africa makes an important contribution to policing to the extent that it adds social and linguistic dimensions, critical-theoretical and sociological approaches relevant to multilingualism, language policy and planning in security contexts over and above conventional security research, which, to date, has been dominated by psychological and anthropological approaches. As a result, this article explores ways in which language and language planning can address security issues in a multilingual context, focusing on the case of South Africa and the South African Police Services. The objective is to analyze multilingualism in relation to security and to draw implications for sociolinguistics of policing studies, and conversely the implications of security studies (and security, policy) for sociolinguistics and multilingualism. This article builds on the limited literature on the sociolinguistics of security and at the same time situates security at the nexus of sociolinguistics and multilingualism in South Africa. The article maintains that while it is true, to a degree, that multilingualism enhances security, the significance and value of multilingualism may be exaggerated especially if language is viewed as disembodied practice. Unless multilingualism is embedded in other semiotic practices that embrace ways in which both historical and contemporary communication in security are framed; it will remain at the periphery of police communication.